2023
DOI: 10.3389/fcell.2023.1211217
|View full text |Cite
|
Sign up to set email alerts
|

Wharton’s jelly mesenchymal stem cells: a concise review of their secretome and prospective clinical applications

Hana Drobiova,
Sardar Sindhu,
Rasheed Ahmad
et al.

Abstract: Accumulating evidence indicates that most primary Wharton’s jelly mesenchymal stem cells (WJ-MSCs) therapeutic potential is due to their paracrine activity, i.e., their ability to modulate their microenvironment by releasing bioactive molecules and factors collectively known as secretome. These bioactive molecules and factors can either be released directly into the surrounding microenvironment or can be embedded within the membrane-bound extracellular bioactive nano-sized (usually 30–150 nm) messenger particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 294 publications
0
7
0
Order By: Relevance
“…However, there is some size overlap between these two types of vesicles. The generation of MVs is an intricate process that involves the redistribution of phospholipids and the contraction of cytoskeletal proteins . The distribution of phospholipids in the plasma membrane is asymmetrical and rigorously controlled by aminophospholipid translocases, such as flippases and floppases.…”
Section: Evs: Biogenesis Composition and Characterization Methodsmentioning
confidence: 99%
“…However, there is some size overlap between these two types of vesicles. The generation of MVs is an intricate process that involves the redistribution of phospholipids and the contraction of cytoskeletal proteins . The distribution of phospholipids in the plasma membrane is asymmetrical and rigorously controlled by aminophospholipid translocases, such as flippases and floppases.…”
Section: Evs: Biogenesis Composition and Characterization Methodsmentioning
confidence: 99%
“…Consequently, examination of miRNAs expression in T-MSCs revealed that the significant downregulation of inflammatory cytokines in treated HMC-1 cells in the presence of T-MSC exosomes may be associated with the overexpression of miR-214-3p, miR-424-5p, miR-126-5p, and miR-302c-3p ( Cho et al., 2022 ). Apart from these findings, it is noteworthy that WJ-MSCs and their exosomes are the most attractive source of stem cells when immunosuppression is needed in inflammatory or infectious conditions ( Drobiova et al., 2023 ). Research suggests that TLR3 and TLR4 ligation may cause a pro-inflammatory phenotype in bone marrow (BM)- and adipose (AD)-MSCs.…”
Section: Exosomes-tlrs Intraction and Infection Controlmentioning
confidence: 99%
“…Several proteomic studies have been performed to clarify the composition of the secretome of MSCs [ 580 , 581 , 582 ]. The complex secretome of MSCs consists, among others, of cytokines, chemokines, growth factors, extracellular matrix components, and extracellular vesicles [ 379 , 413 , 434 , 439 , 463 , 491 , 555 , 580 , 583 , 584 , 585 , 586 , 587 , 588 , 589 , 590 , 591 , 592 , 593 , 594 ] ( Table 5 , Figure 1 and Figure 2 , and Supplementary Figure S1 ). Some of these factors are expressed in sub-population of MSCs, and their expression levels can be affected by interaction with other cell types, by cytokines, and by hypoxia [ 424 , 595 , 596 , 597 , 598 , 599 , 600 ].…”
Section: The Paracrine Function Of Mscsmentioning
confidence: 99%